THE APPLICATION OF COOPERATIVE LEARNING MODEL TYPE OF THINK PAIR SHARE (TPS) TO IMPROVE MATHEMATICS LEARNING RESULTS OF CLASS VIII IN SMP NEGERI 1 SEDAYU BANTUL - Susianti Susianti; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Most students assume that mathematics is a difficult subject that causes many students to make mistakes in solving math problems so that student learning results below. This research aims to improve the results of learning mathematics through cooperative learning model type Think Pair Share (TPS) on class VIII odd semester SMP Negeri 1 Sedayu Bantul academic year of 2016/2017. The research is the act of class research. Subject in this research is all students of class VIII F at SMP Negeri 1 Sedayu Bantul odd semester academic year 2016/2017 as many as 31 students. While the object examined was the improvement of the results of learning mathematics using cooperative learning model type Think Pair Share (TPS) on class VIII F at SMP Negeri 1 Sedayu. Research conducted in two-cycle. Data were collected by using sheets of observation, documentation, interviews, and quiz. The analysis of the data used is descriptive qualitative. The results showed that cooperative learning model type Think Pair Share (TPS) can improve the results of learning mathematics VIII F in odd semester SMP Negeri 1 Sedayu Bantul academic year 2016/2017. This is shown from the results of the mathematics has increased every cycle. On cycle 1 students are thoroughly studied individually there are 20 students with an average of the results of learning mathematics of 83.58 with be passing of classical 66.67% percentage and 100 the highest value and lowest value 40. On cycle 2 has increased is students are thoroughly studied individually there are 24 students with an average value of 88.93 with be passing of classical 80% percentage and 100 the highest value and lowest value 60.Â